Understanding Masculinity in Undergraduate African American Men: A Qualitative Study. (September 2014) - Mincey, Krista; Alfonso, Moya; Hackney, Amy; Luque, John
This study reports findings on views of masculinity with undergraduate Black men, which included interviews and focus groups ( N = 46) with participants ranging in age from 18 to 22 years. Specifically, this study explored how Black men define being a man and being a Black man. Undergraduate Black males at a historically Black college and university ( N = 25) and a predominately White institution ( N = 21) in the Southeastern United States were recruited to participate in this study. Through the use of thematic analysis, findings indicated that three levels of masculinity exist for Black men: what it means to be a man, what it means to be a Black man, and who influences male development. Implications and recommendations for future research and practice are discussed.